Development of VAX128, a recombinant hemagglutinin (HA) influenza-flagellin fusion vaccine with improved safety and immune response - Taylor, David N.; Treanor, John J.; Sheldon, Eric A.; Johnson, Casey; Umlauf, Scott; Song, Langzhou; Kavita, Uma; Liu, Ge; Tussey, Lynda; Ozer, Karen; Hofstaetter, Thomas; Shaw, Alan (Vaccine, 2012)
► Recombinant influenza vaccines differ in safety profiles according to configuration. ► VAX128C was well tolerated up to a dose of 20μg. ► Dose of 1.25 or 2.5μg of VAX128C gave peak GMT was 385, 79% SC and 92% SP. We evaluated the safety and immunogenicity profiles of 3 novel influenza vaccine constructs consisting of the globular head of the HA1 domain of the Novel H1N1 genetically fused to the TLR5 ligand, flagellin. HA1 was fused to the C-terminus of flagellin in VAX128A, replaced the D3 domain of flagellin in VAX128B and was fused in both positions in VAX128C. In a dose escalation trial, 112 healthy subjects 18–49 and 100 adults ≥65 years old were enrolled in a double blind, placebo controlled clinical trial at two centers. Vaccines were administered IM at doses ranging from 0.5 to 20μg. VAX128C was selected for second study performed in 100 subjects 18–64 years old comparing 1.25 and 2.5μg doses. All subjects were followed for safety and sera collected pre- and post-vaccination were tested by hemagglutination-inhibition (HAI). Serum C-reactive protein and cytokine levels were also measured. In the first study high HAI titers and high seroconversion and seroprotection rates were observed at doses ≥2.5μg in adults 18–49. In adults ≥65 years, the vaccines doses of ≥4μg were required to induce a ≥4-fold rise in HAI titer, 50% seroconversion and 70% seroprotection. Based on safety, VAX128A was tested up to 8μg, VAX128B to 16μg and VAX128C to 20μg. Dose escalation for VAX128A was stopped at 8μg because one subject had temperature 101.6°F associated with a high CRP response, VAX128B was stopped at 16μg because of a severe AE associated with a high CRP and IL-6 response. VAX128C was not stopped before reaching the 20μg dose. In the second study VAX128C was well tolerated among 100 subjects who received 1.25 or 2.5μg. The peak GMT was 385 (95%CI 272–546), 79% (71–87%) seroconversion and 92% (84–96%) seroprotection. Flagellin adjuvanted vaccines can be designed to minimize reactogenicity and retain immunogenicity, thereby representing a promising next generation vaccine technology.